Relatório de Estágio Profissional - APRENDER A SER PROFESSOR - Rui Miguel Fão Pinto (2018)
This report reflects a whole school year of internship in a cooperative school in Porto, Portugal. Knowing that this internship has direct consequences in my professional future, making na important aproaching tu the real schools, real pedagogical practices and to it´s protagonists (students and teachers), it was my purpose to hardly commit myself in all the practices of this internship. In the first parto f this report, I intend to let know the life project I´ve beem working. All the experiences and all the social-affective context surely contributes for being a better professional. This life cyvle that I just finished was priceless to me, and I finish it with absolutly sure of my choice of being a teacher. With motivation, commitment and colçabprative work I overcame the difficulties and looking back, in this experience I´m gladly sure that I´ve learned more than I teached. The "área 1" contains all about the planning skills, the evaluation skills and pedagogical practices skills. It was full of challanges and difficulties, but it was full of stratagies to overcome them too. In "área 2" I worried about the school and comunity relationship. In all the activities I planned during I tried to value moments of sharing and socializing between students, teachers and other members of the school comunity, complementing my knowledge as a teacher. In "área 3" I worked on the investigation.The theme was "students attitud towards physical education". With na analytic-descriptive aproach (quiz), answered by 3 classes, it was possible to get a positive answer about the importance of physical education.